Analisis Kriminologis terhadap Kejahatan Judi Online pada Remaja di Lampung Utara - Muhammad Edo Fadely Andaly; Erna Dewi; Emilia Susanti (Asosiasi Peneliti dan Pengajar Ilmu Hukum Indonesia, 2025)
Every teenager should ideally be able to grow and develop well according to their age and as the next generation of the nation, but in reality there are teenagers who commit crimes, one of which is online gambling. Online gambling crimes among teenagers have an impact on other crimes, such as theft, so they must be dealt with optimally. The problem of this research is regarding the criminological analysis of online gambling crimes among teenagers in North Lampung and how the efforts made by the North Lampung Police in dealing with online gambling crimes among teenagers. This research uses a normative and empirical legal approach. The data collection procedure is carried out by means of literature studies and field studies. which are then analyzed qualitatively to obtain conclusions. The results of the research and discussion show that the criminological analysis of online gambling crimes among teenagers in North Lampung in accordance with the Differential Association Theory shows that the cause of teenagers committing online gambling crimes is the interaction, relationship, and communication between teenagers who have never gambled online with other teenagers who have gambled online. In accordance with the Strain Theory, the cause of teenagers committing online gambling crimes is the demands of daily needs. According to Social Control Theory, the cause of teenagers committing online gambling crimes is the lack of supervision from various related parties such as family, schools/educational institutions and law enforcement officers. Efforts to overcome online gambling crimes in teenagers through non-penal means are carried out by socializing child protection and cooperating/coordinating with schools. Penal means are carried out through the process of investigating children who commit online gambling crimes by child investigators based on the Juvenile Justice System Law.